3D-porous electrocatalytic foam based on Pt@N-doped graphene for high performance and durable polymer electrolyte membrane fuel cells. Issue 4 (4th March 2019) - Karuppanan, Karthikeyan K.; Raghu, Appu V.; Panthalingal, Manoj Kumar; Thiruvenkatam, Vijayaraghavan; P., Karthikeyan; Pullithadathil, Biji
Abstract : A new class of sustainable electrocatalysts based on Pt@N-doped graphene foam is developed for the oxygen reduction reaction of PEMFCs. Abstract : A 3D porous nitrogen-doped graphene foam with a uniformly grafted platinum electrocatalyst (2–3 nm) (3D-Pt@N-graphene foam) has been developed using a simple hydrothermal synthesis for high performance proton exchange membrane (PEM) fuel cells. Excellent electrocatalytic activity towards the ORR in acidic medium has been exhibited by Pt@N-graphene foam with a favorable 4-electron transfer pathway resulting in the augmentation of active triple phase boundary sites. The positive shift of onset potential (989 mV) and half wave potential (895 mV) with a high limiting current density of 4.675 mA cm −2 exhibited by the 3D-Pt@N-graphene foam was found to be comparatively greater than that of the Pt/C catalyst with high durability. The presence of pyridinic-N and pyrrolic-N species in the highly compressible 3D-Pt@N-graphene foam contributed to the enhancement of the electrocatalytic activity, while graphitic-N improved the electrical conductivity of the material facilitating the electron transport during the ORR process. Compared to the commercial Pt/C electrocatalyst, the 3D-Pt@N-graphene foam based on a membrane electrode assembly exhibited four times higher power density (394 mW cm −2 ) and current density (1036 mA cm −2 ) owing to the favorable mass transport due to the hierarchical porous network, high specific surface area, nitrogen doping, uniform distribution of Pt nanoparticles and abundant active sites on the support material. The material demonstrates a new rational design for the fabrication of a highly efficient electrocatalyst assembly for flexible PEMFCs.